Vegetable-based biodegradable lubricating oil additives - Maleque, Md. Abdul; Masjuki, H. H.; Sapuan, Salit Mohd (Emerald Group Publishing Ltd., 2003)
Recently, much effort has been focused on research and development of new types of lubricating oil additives to reduce wear and friction in the tribological systems. It has been noted that the use of additives to improve the lubricating capacity and durability of oil plays an important role in the wear and friction process of materials. Due to the environmental problems, many researchers are embarking on the viability of the vegetable-based lubricants. In this article a critical review has been made on vegetable-based lubricant additives with specific properties and application. This article explains the advantages and manufacturing processes of vegetablebased oils, which will give a better understanding of using biodegradable lubricating oil additives. A case study on palm oil methyl ester as an additive has been presented in this paper.